Hospitalized Adult Patient Characteristics Associated With Participation in a Volunteer-Assisted Mobility Program: A Feasibility Study. Issue 4 (October 2020) - Dermody, Gordana; Odom-Maryon, Tamara; Zimmerman, Jennifer; Glass, Courtney
Abstract : Background: Physical inactivity during hospitalization commonly results in functional decline. Structured multidisciplinary programs/approaches may be useful to promote mobility in hospitalized adults. Purpose: The purpose was to determine whether a volunteer-assisted mobility program was feasible to improve the ambulation of hospitalized patients, and examine the characteristics of patients associated with willingness to participate in the program. Methods: A prospective descriptive correlation study was conducted in 2 acute care units. A volunteer-staffed program was implemented with the aim of improving the ambulation of hospitalized patients. Results: Hospitalized patients (N = 490) were approached, with 39.2% (n = 192) agreeing to ambulate an average of 109.7 m (interquartile range = 51.45-172.2 m). Patients with a low clinical frailty score, high body mass index, or physical therapy order were more likely to participate in the volunteer-assisted mobility program. Conclusions: The findings suggest that a volunteer-assisted interdisciplinary program is a feasible way to promote the ambulation of some patients. Abstract : Supplemental Digital Content is Available in the Text.